Letter - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
806-0003-001 Tele: Maida Vale 1384. 4, Aberdare Gardens, Hampstead, LONDON, N.W.6. 3rd April, 1939. Miss B. Barclay Carter, Hon. Secretary, People and Freedom Group, 32, Chepstow Villas, LONDON, W.11. Dear Madam, I very much regret that owing to the fact that I only recently arrived from the West Indies, where I had gone by special invitation, I was unable to attend the meeting of the People and Freedom Group last Wednesday night. As I have been away two months I am not sure whether anything special has happened in my absence, but if there is anything I will be glad if you will let me know. I am still of the opinion that we should start to organise the Catholics from the bottom and not from the top, and I am still hoping to try to devise some means of doing so which will not arouse opposition. I propose to send you a list of Trade Union Secretaries throughout Great Britain and Trades and Labour Councils, and I will try to do so in the near future. Yours sincerely, 292C/806.1/1/3